Campur Kode dan Alih Kode: Studi Dalam Novel Jilbab Traveler Love Sparks in Korea Karya Asma Nadia - Aliffatul Saqdiah; Novia Juita (Persona: Kajian Bahasa dan Sastra, 2022)
Due to Indonesia's high population density and language abundance, language-related phenomena such as code mixing, code switching, and bilingualism occur. As a result, Indonesians have become bilingual and multilingual and speak many languages. The purpose of this study is to explain the various types of code switching and mixing contained in Asma Nadia's novel until its appearance. The findings obtained through the use of this descriptive approach were incorporated into qualitative research. The research data are in the form of dialogue and author narration, containing code switching and code mixing. This finding is based on reading, recording, and classifying data using the observation method. Triangulation methods are very helpful for validating data. Data analysis revealed that there is only one type of code mixing and code switching in this novel by Asma Nadia. Exit code mixing obtained as many as 376 data and code switching as many as 94 data. One type of code mixing and one type of code switching are also caused by five factors. From these findings, readers can find out the various types of code mixing and code switching and their causes.